Impact of augmentation strategy variations on the mechanical characteristics of patients with osteoporotic proximal humerus fractures with medial column instability - Xiao, Guoqing; Zhang, Xiang; Duan, Alin; Li, Jian; Chen, Jialei (Frontiers in Bioengineering and Biotechnology, 2024)
Low bone density and lack of medial support are the two most important factors affecting the stability of locking plate fixation for osteoporotic proximal humeral fractures (PHFs). This study aimed to compare the biomechanical characteristics of PHILOS locking plates combined with calcar screws, bone cement, fibular allografts, and medial locking plate support strategies for treating osteoporotic PHFs with medial column instability. A three-part osteoporotic PHF (AO 11-B3.2) model with metaphyseal loss was generated using 40 synthetic humeri and fixed via four distinct medial support strategies. All models were mechanically tested to quantify the mechanical characteristics. Subsequently, finite element models were created for each biomechanical test case. The stress distribution and displacement of the four different fixation structures were analyzed using finite element analysis. The results demonstrated that the PHILOS locking plate combined with the medial locking plate, exhibited the greatest stability when subjected to axial, shear, and torsional loading. Furthermore, the PHILOS locking plate combined with bone cement showed structural stability similar to that of the PHILOS locking plate combined with fibular allograft but with lower stress levels on the fracture surface. In conclusion, the PLP-MLP fixation structure showed superior biomechanical properties under axial, shear, and torsional loading compared to other medial support methods. Repairing the medial support when treating osteoporotic PHFs with medial column instability can enhance the mechanical stability of the fracture end in both the short and long term.